“They are with me, they keep me updated, they help me”. Practices in use of information and communications technology, and communication by young people in the South of the state of Yucatan, in Mexico - Cornejo Portugal, Inés (2020)
In Mexico, the municipalities of Dzán, Oxkutzcab, Santa Elena and Ticul are located in the South of the State of Yucatán. They are characterized by citruses production, the high migration rate towards the United States, the educational backwardness and high levels of poverty. In this context, residentes have access to different technologies devices and platforms that they use por specif purposes. We assume that the practice tecnology use seem to be determined by institucional education, and by the need for comnunication to stablish or mainntain some kind of emotional bond with the parents or relatives who emigrated and settled permanently in United States.